Dinuclear salen cobalt complex incorporating Y(OTf)3: enhanced enantioselectivity in the hydrolytic kinetic resolution of epoxides. Issue 101 (29th September 2015) - Patel, Deepak; Kurrey, Ganesh Ram; Shinde, Sandip S.; Kumar, Pradeep; Kim, Geon-Joong; Thakur, Santosh Singh
Abstract : Yttrium triflate present in dinuclear salen cobalt complex not only shows a promoting effect on electron transfer, but also assists in the asymmetric ring opening of epoxides with water efficiently. Abstract : The activation of inactive Jacobsen's chiral salen Co(ii ) (salen = N, N ′-bis(3, 5-di- tert -butylsalicylidene)-1, 2-cyclohexanediamine) compound is attained by dinuclear chiral salen Co(iii )–OTf complex formation with yttrium triflate. The yttrium metal not only displays a promoting effect on electron transfer, but also assists in forming two stereocentres of a Lewis acid complex with Co(iii )–OTf. We found that the binuclear Co-complex significantly enhanced reactivity and enantioselectivity in the hydrolytic kinetic resolution of terminal epoxides compared to its analogous monomer and kinetic data are also consistent with these results.